2022
DOI: 10.3389/fcell.2022.807149
|View full text |Cite
|
Sign up to set email alerts
|

Protein Posttranslational Signatures Identified in COVID-19 Patient Plasma

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a highly contagious virus of the coronavirus family that causes coronavirus disease-19 (COVID-19) in humans and a number of animal species. COVID-19 has rapidly propagated in the world in the past 2 years, causing a global pandemic. Here, we performed proteomic analysis of plasma samples from COVID-19 patients compared to healthy control donors in an exploratory study to gain insights into protein-level changes in the patients caused by SARS-CoV-2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…Numerous inflammatory mediators were associated with COVID‐19 patient death (IL‐6, IL‐8, CXCL10 and CCL‐2, CCL‐7, CCL‐8, CCL‐20). 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Unique to our study, and as compared to others, 14 were the chemokine blast, ECM remodelling and collagen turnover due to fibroblast activity. Our data also suggested altered coagulation, activated platelets, deficient T‐ and B‐cell homing, T‐cell exhaustion, deficient organ regeneration and kinases that can be ultimately manipulated by cancer repurposed dugs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Numerous inflammatory mediators were associated with COVID‐19 patient death (IL‐6, IL‐8, CXCL10 and CCL‐2, CCL‐7, CCL‐8, CCL‐20). 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 Unique to our study, and as compared to others, 14 were the chemokine blast, ECM remodelling and collagen turnover due to fibroblast activity. Our data also suggested altered coagulation, activated platelets, deficient T‐ and B‐cell homing, T‐cell exhaustion, deficient organ regeneration and kinases that can be ultimately manipulated by cancer repurposed dugs.…”
Section: Discussionsupporting
confidence: 56%
“… 4 , 5 , 6 , 7 The uncertainty in disease severity and progression makes uniform COVID‐19 management difficult, indicating that patients could benefit from a precision medicine approach. 8 , 9 , 10 , 11 , 12 Among the next generation technologies used to investigate COVID‐19, 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 this study is unique as we dissect the cytokine storm and the organ damage profiles.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we analyzed the plasma protein pro les of Long-COVID outpatients, and compared with ageand sex-matched acutely ill COVID-19 inpatients and healthy control subjects. The plasma proteome was deconvoluted into cell-type pro les and signaling pathways, as well as speci c organ systems based on previously curated biomarkers [20][21][22][23][24][25][26][27][28][29]. Several biomarkers were dramatically elevated in Long-COVID patients and taken together these markers pinpointed immune triggered vascular proliferation which is mediated by hypoxia with a strong effect on brain and heart function [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…1). Broadening its importance, recent studies have even demonstrated links between ATE1-catalyzed arginylation and certain types of cancer 45 , while connections to the virulence of serious human infectious agents such as the human immunodeficiency virus (HIV) 46 and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2; cause of the COVID-19 pandemic) are emerging 47 (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%